Adolescent rats are protected from the conditioned aversive properties of cocaine and lithium chloride - Schramm-Sapyta, Nicole L. (2006)
In humans, most drug use is initiated during adolescence and adolescent users are more likely to become drug-dependent than adult users. Repeated, high levels of use are required for the transition from use to addiction. Individual levels of drug use are thought to result from a balance between the pleasant or rewarding and the unpleasant or aversive properties of the drug. Repeated high levels of drug use are required for the transition from drug use to dependence. We hypothesized that diminished aversive effects of drugs of abuse during adolescence might be one reason for higher rates of use and addiction during this phase. We therefore tested adolescent and adult CD rats in single-dose cocaine conditioned taste aversion (CTA) at a range of doses (10–40 mg/kg), and examined whether various behavioral markers of addiction vulnerability were correlated to outcome in cocaine CTA. We found that adolescents are indeed less susceptible to cocaine CTA. In fact, age was the predominant predictor of CTA outcome, predominating over measures of novelty-seeking, anxiety, and stress hormone levels, which are all known to be related to drug intake in other models. Furthermore, we found that adolescent rats are also less susceptible to conditioned taste aversion to a low dose of a non-addictive substance, lithium chloride. These results suggest that one explanation for elevated drug use and addiction among adolescents is reduced aversive or use-limiting effects of the drugs. This contributes to our understanding of why adolescence is a particularly vulnerable period for development of drug abuse.